Recent improvements and challenges in Fukushima: prefecture's economy and living environment. Issue 4 (24th July 2014) - Ofuji, Kenta
<x xml:space="preserve">Abstract</x> Today as we approach the 3‐year mark since the earthquake disaster and nuclear accident, Fukushima Prefecture's economy is gradually improving, albeit not yet completely, and the living environment in urban areas is showing signs of recovery. Yet much remains to be done to reassure people, who have still not returned home since evacuating, about their fears concerning radiation, and to dispel harmful rumors about the tourism and the farming and fishing industries. In this article, I raise three issues: (1) decontamination and target dose, (2) contaminated water and revival of the fishing industry, and (3) a vision for the industrialization of renewable energy; and present examples of the progress made in recent efforts in these three issues to close the gap between the ideal and reality. WIREs Energy Environ 2015, 4:307–315. doi: 10.1002/wene.139 For further resources related to this article, please visit the WIREs website. Conflict of interest: The author has declared no conflicts of interest for this article.